2016
DOI: 10.1038/srep30617
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of QuantiFERON-TB Gold Plus for Detection of Mycobacterium tuberculosis infection in Japan

Abstract: Performance of interferon-γ (IFN-γ) release assays still needs to be improved. The data on the performance of QuantiFERON-TB Gold Plus (QFT-Plus), a new-generation of QFT assay are limited. This study evaluated the diagnostic performance of QFT-Plus, and compared to that of QuantiFERON-TB Gold In-Tube (QFT-GIT). Blood samples were collected from 162 bacteriologically confirmed tuberculosis (TB) patients and 212 Mycobacterium tuberculosis-uninfected volunteers; these samples were then tested with QFT-GIT and QF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
43
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 28 publications
(30 reference statements)
11
43
1
Order By: Relevance
“…The new CD8+ -specific peptides have been added to increase the sensitivity of the test because it has been shown that Mtb-specific CD8+ T-cells are mainly associated to active TB [44,45,46,47]. The first data on the performance of QuantiFERON TB Plus were reported recently [48,49,50]. When compared with the previous test version of QFT-GIT [50], equal sensitivity of the new generation QFT-plus was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The new CD8+ -specific peptides have been added to increase the sensitivity of the test because it has been shown that Mtb-specific CD8+ T-cells are mainly associated to active TB [44,45,46,47]. The first data on the performance of QuantiFERON TB Plus were reported recently [48,49,50]. When compared with the previous test version of QFT-GIT [50], equal sensitivity of the new generation QFT-plus was observed.…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that the difference in IFN‐γ production between the two antigen tubes (TB2 − TB1) provides an estimate of the specific CD8 response, and this could possibly indicate recent infection and disease activity. The QFT‐Plus has been shown to have high concordance with the QFT‐GIT and to be more strongly associated with exposure . Large‐scale studies are awaited to see if the QFT‐Plus can improve sensitivity and fulfil currently unmet clinical needs in identifying those with active disease, those with recent LTBI and for the monitoring of response to anti‐TB treatment.…”
Section: Diagnostic Tests For Ltbimentioning
confidence: 99%
“…The QFT-Plus has been shown to have high concordance with the QFT-GIT and to be more strongly associated with exposure. 47,48 Large-scale studies are awaited to see if the QFT-Plus can improve sensitivity and fulfil currently unmet clinical needs in identifying those with active disease, those with recent LTBI and for the monitoring of response to anti-TB treatment.…”
Section: New Tests For Ltbimentioning
confidence: 99%
“…This was recently suggested in a cohort of 119 patients with active TB (84.9% sensitivity with QFT-Plus TB2 versus 80.7% with TB1) (16). However, follow-up studies directly comparing QFT to QFT-Plus in active TB patients did not show a difference in sensitivity (15,17,18). Furthermore, the sensitivity and specificity of QFT-Plus for LTBI in low-risk individuals, such as low-risk North American HCWs, remains to be determined.…”
mentioning
confidence: 93%